2021
DOI: 10.3390/molecules27010188
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A and 2′R-Ochratoxin A in Selected Foodstuffs and Dietary Risk Assessment

Abstract: The aim of this study was to estimate the contamination of grain coffee, roasted coffee, instant coffee, and cocoa purchased in local markets with ochratoxin A (OTA) and its isomerization product 2′R-ochratoxin A (2′R-OTA), and to assess risk of dietary exposure to the mycotoxins. OTA and 2′R-OTA content was determined using the HPLC chromatography with immunoaffinity columns dedicated to OTA. OTA levels found in all the tested samples were below the maximum limits specified in the European Commission Regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…To date, 2'ROTA has been found in food products that required elevated manufacturing temperatures. Although diastereomer levels were relatively low, the presence of the isomer was confirmed in coffee, cocoa, bread and other products (Bittner et al, 2015;Zapa snik et al, 2022;Bryła et al, 2023).…”
Section: Chemistrymentioning
confidence: 93%
“…To date, 2'ROTA has been found in food products that required elevated manufacturing temperatures. Although diastereomer levels were relatively low, the presence of the isomer was confirmed in coffee, cocoa, bread and other products (Bittner et al, 2015;Zapa snik et al, 2022;Bryła et al, 2023).…”
Section: Chemistrymentioning
confidence: 93%
“…OTA in the same studies was found to be most prevalent in cocoa products (81%), dried fruit (73%), and wine (59%), but it was most prevalent in red or sweet wine as compared to the other wines [ 6 , 26 ]. In addition to cocoa products, coffee and chocolate were also reported to contain high contamination levels of the same mycotoxin [ 27 , 28 , 29 ]. A high prevalence of OTA was also found in wheat-based products (94%) in Canada [ 23 ], but the highest OTA levels have been reported in countries in Southern Europe [ 26 ].…”
Section: Mycotoxin Prevalence and Current Regulationsmentioning
confidence: 99%
“…OTA (Liang et al., 2015; Zapasnik et al., 2022) is among the higher toxicity, including nephrotoxicity, teratogenicity, and carcinogenicity, and serves as an immunosuppressor that lowers the immunity of the human body. OTA is frequently found in wheat, maize, cereals, and other crops as raw materials.…”
Section: Application Of Dna Tweezers In Food Testingmentioning
confidence: 99%